KKN TEMATIK MAHASISWA UMSU DALAM PEMBUATAN PETA DESA WISATA SUKA MAKMUR - Suhaila Nafisa; Rahmad Muliadi, Wahyuti Situmeang, Edisah Putra Nainggolan (Adiba Aisha Amira, 2024)
Thematic KKN activities of Muhammadiyah University of North Sumatra (UMSU) students in Suka Makmur Village, Kutalimbaru District, Deli Serdang Regency aim to advance village tourism through the creation of a tourist village map. This research uses a descriptive qualitative approach with data collection methods through participatory observation, in-depth interviews, and documentation. The program was implemented for 4 months and resulted in an informative village map sign that contains complete details about the geographical structure, infrastructure, and important locations in Suka Makmur Village. The map-making process included needs recognition, activity planning, and implementation, which included mapping tourism potential, creating a digital map, and briefing the Tourism Awareness Group. The results showed high community participation in the development of the village tourism map, which had a positive impact on the promotion of the village's tourism potential to the wider community. The sustainability of the program is ensured through training to villagers on updating map information and developing tourism promotion content.